2019
DOI: 10.3389/fimmu.2019.00283
|View full text |Cite
|
Sign up to set email alerts
|

LL37 Inhibits Aspergillus fumigatus Infection via Directly Binding to the Fungus and Preventing Excessive Inflammation

Abstract: The incidence of Aspergillus fumigatus infection and the rate of resistance to antifungal drugs have sharply increased in recent years. LL37 has been reported as a host defense peptide with broad-spectrum antibacterial activities. However, the role of LL37 during A. fumigatus infection remains unclear. Here, we examined the interaction between LL37 and A. fumigatus and found that synthetic LL37 could directly bind to the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 38 publications
(40 reference statements)
3
26
0
1
Order By: Relevance
“…Recently, 1 µM LL-37 has been reported to promote the growth of A. fumigatus when grown in Sabouraud dextrose broth for 24 and 48 h [12]. In contrast with this, another recent study reported that 1-20 µM LL-37 inhibits mycelial growth of A. fumigatus in a dose-dependent manner when grown in RPMI for 12 h [13]. These contrasting observations are not easily explained, although differences between strains, AMP concentrations and experimental conditions probably account for these contrasting results.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, 1 µM LL-37 has been reported to promote the growth of A. fumigatus when grown in Sabouraud dextrose broth for 24 and 48 h [12]. In contrast with this, another recent study reported that 1-20 µM LL-37 inhibits mycelial growth of A. fumigatus in a dose-dependent manner when grown in RPMI for 12 h [13]. These contrasting observations are not easily explained, although differences between strains, AMP concentrations and experimental conditions probably account for these contrasting results.…”
Section: Discussionmentioning
confidence: 94%
“…AMPs are key components of the human defences against invading microorganisms. Over 100 human AMPs have been described, ranging in size from 10 to 149 amino acids, and have net charges Histones 5-150 µg/mL [29,30] Inhibitory activity against Candida albicans reported at 26 µg/mL [34] LL-37 0.5-10 nM [25][26][27][28] Inhibitory activity against A. fumigatus at 20 µM [15] and growth promotion activity against A. fumigatus at 1 µM [12,13] lactoferrin 1-10 µM [18][19][20][21][22] Inhibitory activity against C. albicans at 0.25-2.5 µM [35] β-defensin-1 0.2-2 nM [6,23] Inhibitory activity against C. albicans at 7 µM [36] This study aimed to characterise the anti-Aspergillus activity of these AMPs, and to determine whether clinical isolates obtained from various patient populations show differences in their susceptibilities to specific AMPs. In addition, we assessed whether changes in AMP susceptibility occur as a result of in-host adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…paratuberculosis (MAP), a bacterium causing chronic diarrheic intestinal infections in domestic and wild ruminants, by increasing bacterial uptake in murine macrophages. In addition, macrophage treatment with LL-37 suppresses TLR2 upregulation and thereby the production of tissue-damaging inflammatory cytokines released during MAP infection (153), as well as during A. fumigatus infection (154).…”
Section: Cathelicidin-mediated Tlr Regulation In Vitromentioning
confidence: 99%
“…The immunostaining protocol was adapted from Luo et al (29). F. oxysporum was grown in 5 ml malt extract broth from a starting concentration of 2.9 × 10 5 spores/ml.…”
Section: Peptide Hyphal Binding and Immunofluorescencementioning
confidence: 99%
“…In addition, our immunofluorescence data demonstrate that Daisho2 can interact in vitro with at least one filamentous fungus that it targets. Antifungal peptides, such as mammalian LL-37 and plant defensin NaD1, also bind hyphae of fungal pathogens against which they are active (29,37). The Daisho2 peptide's ability to bind fungal hyphae could indicate an antimicrobial function.…”
Section: Activity Of Daisho Peptidesmentioning
confidence: 99%